POLA ASUH ORANGTUA PADA ANAK TUNA RUNGU DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA - Sipayung, Bram Leonardo; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Kelurahan Sail Tenayan Raya District. This study clims to know the prential care patterns in Kelurahan Sail Tenayan Raya District was eximined by qualitative descriptive analysis. In this study, the writer collected the data by direct interview technique in research location. The responden in this study amount 7 people, namely 5 the mother of the deaf children, a teacher and a doctor. The instruments used in this study are the questions as interview materials, photos and video recording too. The result of this study indicate that the parenting tendenas applied by parent to deaf children is permissive, which provide loose supervision to the children to something without adequate supervision from their parents. The parenting implemented through family function. The deafness which is happened by children make the parents difficullty for keeping even communicating with the deaf children. The deaf children use sign language and action as a communication between parent and other peolple around them. The role of teachers in the school is that continue to educate children, shaping the character, the child personality and improve the language or intellectual ability of the child. The role of doctors is very important in the people handlig with hearing impairment including children who are deafned. Doctors play a role in dealing with deaf children.Key words : Parenting, Parents, Deafness.